"That's what I'm supposed to do at work": gendered labor, self-care, and overdose risk among women who use drugs in Vancouver, Canada. Issue 3 (27th May 2022) - Collins, Alexandra B.; McNeil, Ryan; Czechaczak, Sandra; Boyd, Jade
ABSTRACT: Through rapid ethnography undertaken in Vancouver, Canada's Downtown Eastside – one of Canada's overdose epicenters – this article examines how gendered expectations of labor shape overdose risk for structurally vulnerable women and gender diverse people who use drugs. Drawing on two participant narratives, we explore how structural, symbolic, and everyday violence frame the lives of women and gender diverse people who use drugs in ways that drive their overdose risk as they balance self-care with caretaking, paid work, and basic survival. This article underscores the need for structural reform of peer overdose response work and funding for gender-attentive harm reduction and ancillary supports to better mitigate overdose risk for these populations.